انعكاس دلالات الأصوات على السياق الكلي للنص : آيات الترغيب والترهيب نموذجا - تجاني، سعدة السنوسي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research addresses the “Inversion of Voices Denotations on Overall Context of Texts - The Case of Exhortation and Intimidation Verses” where the researcher listed selected verses contained in Chapter Qaaf through Chapter Al Naas as samples for the study. The research adopted the descriptive analytical approach and it aims at explaining the extent of voice inversion on the overall text, while focusing on loud and whispered letters and the extent of their engagement with the exhortation and intimidation verses. This is done by demonstrating the opinions of former and new scholars about the issue of voice engagement with denotation, explaining the methods of exhortation and intimidation adopted in the Qur'an, and the concept of loud and whispered letters and the extent of their engagement with exhortation and intimidation verses. The researcher concluded that there is a remarkable and clear difference in the repetition of whispered and loud characters among the exhortation and intimidation verses in terms of amount and percentage, though it is statistically different because the value of the extracted denotation from SPSS was 0.06 which is more than 0.05.